2023
DOI: 10.12688/f1000research.132106.2
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa L. seed extracts promote wound healing progress by activating VEGF and PDGF signaling pathways: An in vitro and in silico study

Abstract: Background: A significant area of clinical research is the development of natural wound healing products and the management of chronic wounds. Healing wounds with medicinal plants has been a practice of ancient civilizations for centuries. Nigella sativa L (N. sativa) is a medicinal plant that has several pharmacological properties. Methods: The present study evaluated the wound healing properties of Nigella sativa L. (N. sativa) seed extracts using normal cell lines such as normal human dermal fibroblasts (NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Some studies also reported that oleanolic acid, Panaxadiol, Ursolic acid, Withaferin A, Hecogenin were potential against GFRs [32] . In addition phytochemicals like Tricyclo (20.8.0.0 (7,16) triacontane, 1 (22), 7(16)‐diepoxy‐ (543764), Adaphostin, Obeticholic acid, Methylphenidate, HFB, Hypophyllanthin, Vitamin E, Clonitazene, Humulane‐1,6‐dien‐3‐ol from Nigella sativa L. seed extract [33] . Some studies also find that 1‐Penten‐3‐ol, Ethyl benzoate, Methanol, α Cubenene, α Guinea, β Bourbonene, β‐Cubebene, Eucalyptol were potential inhibitors against VEGFR [34] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies also reported that oleanolic acid, Panaxadiol, Ursolic acid, Withaferin A, Hecogenin were potential against GFRs [32] . In addition phytochemicals like Tricyclo (20.8.0.0 (7,16) triacontane, 1 (22), 7(16)‐diepoxy‐ (543764), Adaphostin, Obeticholic acid, Methylphenidate, HFB, Hypophyllanthin, Vitamin E, Clonitazene, Humulane‐1,6‐dien‐3‐ol from Nigella sativa L. seed extract [33] . Some studies also find that 1‐Penten‐3‐ol, Ethyl benzoate, Methanol, α Cubenene, α Guinea, β Bourbonene, β‐Cubebene, Eucalyptol were potential inhibitors against VEGFR [34] .…”
Section: Resultsmentioning
confidence: 99%
“…[32] In addition phytochemicals like Tricyclo (20.8.0.0 (7,16) triacontane, 1 (22), 7(16)-diepoxy-(543764), Adaphostin, Obeticholic acid, Methylphenidate, HFB, Hypophyllanthin, Vitamin E, Clonitazene, Humulane-1,6-dien-3-ol from Nigella sativa L. seed extract. [33] Some studies also find that 1-Penten-3-ol, Ethyl benzoate, Methanol, α Cubenene, α Guinea, β Bourbonene, β-Cubebene, Eucalyptol were potential inhibitors against VEGFR. [34] It is also reported that Sesamin, Fargesin, Longamide, Piperlonguminine, Eriodictyol, Epicatechin, Scutellarin, Tetrandrine, Basic acid and Ginkgolide were potential inhibitors for VEGF.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%